FUNDAMENTAL ASPECTS OF COMMUNICATION MANAGEMENT, IN THE CASE OF PUBLIC ADMINISTRATION - Pocovnicu, Dorian (Studies and Scientific Researches. Economics Edition, 2014)
Efficient communication is one the most important instruments used for the purpose of generating change inside and outside an organization. It can contribute to adjusting attitudes and the manner of approaching the present and future challenges and to changing behavioral patterns. The mission and the objectives of organizational communication are highly interrelated with organizational change and environment characteristics, in which the organization functions. The communication performed by the public administration institution outside is an institutional communication, extra-organizational, which presents the following purposes: strengthening its image, stimulating an environment of trust and affinity from the citizens (Kotler & Lee, 2007). We are of opinion that the management of communication performed by a public administration institution features three fundamental aspects, relevant for institutional communicators when designing and managing the institutional communication: communication efficiency, communication process and the implications of the new information and communication technologies (ICT) for this process.